2012
DOI: 10.1371/journal.pone.0045261
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Multi-Organ Lymphangiectasia Resulting from Temporal Deletion of Calcitonin Receptor-Like Receptor in Adult Mice

Abstract: Adrenomedullin (AM) and its receptor complexes, calcitonin receptor-like receptor (Calcrl) and receptor activity modifying protein 2/3, are highly expressed in lymphatic endothelial cells and are required for embryonic lymphatic development. To determine the role of Calcrl in adulthood, we used an inducible Cre-loxP system to temporally and ubiquitously delete Calcrl in adult mice. Following tamoxifen injection, Calcrlfl/fl/CAGGCre-ER™ mice rapidly developed corneal edema and inflammation that was preceded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 44 publications
4
54
0
Order By: Relevance
“…Global deletion of the gene coding for the AM receptor, Calcrl, has been shown to induce multiorgan lymphangiectasia, resulting from dilated lymphatic vessels across several vascular beds (23). Since Calcrl is commonly expressed in several cell types, including cells outside the vasculature, to distinguish the role of Calcrl in lymphatic cells compared with its role in other cell types in contributing to lymphangiectasia, we deleted Calcrl from the adult mouse lymphatic endothelium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Global deletion of the gene coding for the AM receptor, Calcrl, has been shown to induce multiorgan lymphangiectasia, resulting from dilated lymphatic vessels across several vascular beds (23). Since Calcrl is commonly expressed in several cell types, including cells outside the vasculature, to distinguish the role of Calcrl in lymphatic cells compared with its role in other cell types in contributing to lymphangiectasia, we deleted Calcrl from the adult mouse lymphatic endothelium.…”
Section: Resultsmentioning
confidence: 99%
“…These signaling partners are crucial for embryonic development since genetic deletion of Calcrl, Adm, or Ramp2 causes midgestation lethality due to arrested lymphangiogenesis in mice (20)(21)(22). In adult mice, the inducible, global genetic deletion of the Calcrl gene causes systemic lymphatic insufficiency in a multitude of lymphatic vascular beds, leading to corneal edema, distal limb edema, and lymphangiectasia (23). Since CLR is expressed in many cell types and tissues, we developed a genetic mouse model with inducible deletion of the Calcrl gene in lymphatic endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…Other models involving gene deletions or implantation of cells from human lymphatic malformations have been used to mimic human lymphatic disorders (37)(38)(39)(40). These models have proven useful in characterizing these conditions but are yet to be used to study the regression of abnormal lymphatics.…”
Section: Attributes and Limitations Of The Ccsp/vegf-c Mouse Model Ofmentioning
confidence: 99%
“…Immunohistochemical staining to characterize the ECs of SC revealed that they were positive for certain lymphatic and blood endothelial markers, including PROX1, integrin α9, CD31, lin, exhibited corneal edema, inflammation, and dilated corneoscleral lymphatic vessels (12). Earlier this year, Truong et al discovered high expression of the lymphatic transcription factor prospero-related homeobox 1 (PROX1) on SC endothelium in the eye (13), linking expression of the lymphatic fate determinant PROX1 to a structure within the eye.…”
Section: Lymphatics In the Eye?mentioning
confidence: 99%